1991
DOI: 10.1149/1.2085863
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimization of the Step Coverage of Tungsten LPCVD in Trenches and Contact Holes

Abstract: A model is presented to calculate the step coverage of blanket tungsten low pressure chemical vapor deposition (W-LPCVD) from tungsten hexafluoride (WF6). The model can calculate tungsten growth in trenches and circular contact holes, in the case of the WF6 reduction by H2, Sill4, or both. The step coverage model predictions have been verified experimentally by scanning electron microscopy (SEM). We found that the predictions of the step coverage model for the Ha reduction of WF 8 are very accurate, if the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 17 publications
2
48
0
Order By: Relevance
“…In order to eliminate the effects of surface tension in small geometries, vapor-phase processes are preferred. Considerable experimental and modeling work has been devoted to conformal inorganic coatings synthesized via CVD [1][2][3][4] or atomic layer deposition (ALD). [5] Recent work has shown that ALD can be used to coat the interior of nanoporous aerogels with copper.…”
Section: Introductionmentioning
confidence: 99%
“…In order to eliminate the effects of surface tension in small geometries, vapor-phase processes are preferred. Considerable experimental and modeling work has been devoted to conformal inorganic coatings synthesized via CVD [1][2][3][4] or atomic layer deposition (ALD). [5] Recent work has shown that ALD can be used to coat the interior of nanoporous aerogels with copper.…”
Section: Introductionmentioning
confidence: 99%
“…This formula is, in principle, only valid for cylindrical holes with an infinite depth and should be multiplied with the Clausing factor for holes with a finite depth. 26 However, to allow for a straightforward modification of this formula for other geometries, as done below, the uncorrected formula (2) was used in this work. For holes with a square cross section defined by the width w, the diffusivity can be estimated as 27…”
Section: B Analytic Approximationsmentioning
confidence: 99%
“…A first approach has been to model CVD in small cylindrical holes as a Knudsen-diffusion-and-heterogeneous-reaction process [51,52] based on a one-dimensional pseudo-continuum mass balance equation for the species concentration along the depth of a pore, using a Knudsen diffusion coefficient which is proportional to the pore diameter. This approach has been applied in two-dimensional models as well [53].…”
Section: Feature Scale Cvd Modelsmentioning
confidence: 99%